Diterpenoid alkaloids from the roots of Aconitum brachypodum Diels. Issue 9 (1st September 2016) - Yang, Li-Guo; Zhang, Ying-Jie; Xie, Jia-Ying; Xia, Wei-Jun; Zhang, Hai-Yuan; Tang, Meng-Yun; Mei, Shuang-Xi; Cui, Tao; Wang, Jing-Kun; Zhu, Zhao-Yun
Abstract: A new diterpenoid alkaloid, named bullatine H (1 ), along with 10 known diterpenoid alkaloids were isolated from the roots of Aconitum brachypodum Diels (Ranunculaceae). The structure of1 was elucidated by analysis of its spectroscopic data. It should be noted that compound1 is the first example with 11, 13-dioxygenated denudatine-type diterpenoid alkaloid isolated from Aconitum brachypodum .